Численный метод решения гиперсингулярного интегрального уравнения второго рода - Костенко, А.В. (Український математичний журнал, 2013)
Запропоновано чисельний метод розв'язання гіперсингулярного інтегрального рівняння другого роду — узагальнення відомого методу. При додаткових припущеннях доведено теорему існування та єдиності розв'язку. Отримано оцінку швидкості збіжності наближеного розв'язку до точного. А numerical method for the solution of a hypersingular integral equation of the second kind obtained as a generalization of the well-known method is proposed. The existence and uniqueness theorem is proved under additional assumptions. The rate of convergence of an approximate solution to the exact solution is obtained.